Ultrafast Decay of Interlayer Exciton in WS2/MoSe2 Heterostructure Under Pressure - Zhiying Bai; He Zhang; Jiaqi He; Dawei He; Jiarong Wang; Wenwen Wu; Yinglin Zhang; Wenjie Wang; Yongsheng Wang; Xiaohui Yu; Xiaoxian Zhang (Advanced Electronic Materials, 2025)
Abstract Atomically thin transition metal dichalcogenides (TMDs) heterostructures provide a rich platform for exploring fascinating physics and engineering strategies. A pressure strategy is developed to effectively manipulate the physical properties in such heterostructures. However, there is still a lack of studies on the corresponding pressure‐modulated evolution of carrier dynamics, which is crucial to the performance of electronic and optoelectronic devices. Here, utilizing the diamond anvil cell, the interlayer exciton dynamics of WS2/MoSe2 heterostructure are subtly manipulated by pressure. Intriguingly, with pressure modulation, the enhanced interlayer coupling accelerates the recombination of spatially separated electron and hole, which significantly shortens the interlayer exciton lifetime from 37.10 ps at 0.0 Gpa to 3.03 ps at 2.2 Gpa. For comparison, the intralayer exciton lifetime of monolayer MoSe2 is increased due to the transition of direct to indirect bandgap under pressure. Furthermore, the pressure‐regulated band structure and interlayer coupling are confirmed by photoluminescence and Raman spectroscopy. The results demonstrate that pressure provides a powerful tuning knob for interlayer exciton relaxation of TMDs heterostructure, which is attractive to various electronic and optoelectronic applications based on such heterostructure.